Antibiotic patterns of ampicillin, streptomycin, and tetracycline in stray cats - Wibisono, Freshinta Jellia; Widiasih, Dyah Ayu; Fardiansyah , Al; Isnaeni, Mutia; Mentari , Andi Oktaviana; Qurratu'ain , Seryna Hasna; jalal , Ismul; Islam, Afif Fajrul (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2024)
This research was conducted to determine the presence of Escherichia coli bacteria in anal swabs of wild cats, determine the existence of antibiotic resistance in Escherichia coli bacteria, and determine resistance patterns in Escherichia coli bacteria. A total of 90 swab samples were taken, consisting of 30 anal swab samples from wild cats in the East Surabaya Region and 30 anal swab samples from wild cats in the West Surabaya Region. Samples were tested at the Veterinary Health Laboratory, Faculty of Veterinary Medicine, Wijaya Kusuma University, Surabaya. Samples were brought using buffered peptone water. Samples were isolated and identified using Mac Conkey Agar differential selective media. Isolates identified as Escherichia coli were then subjected to gram staining tests, biochemical tests, and sensitivity tests to determine the presence of resistance and multidrug resistance. The results of the study showed that 95.5% (86/90) of the samples contained Escherichia coli bacteria and the results of the sensitivity test showed that there was antibiotic resistance showing that 25.5% (22/86) were resistant to the antibiotic ampicillin, 19.3% (17/86) were resistant to tetracycline antibiotics, and 13.9% (12/86) were resistant to streptomycin antibiotics. The resistance test results showed that multidrug resistance in Escherichia coli bacteria taken from cat anal swabs was 6.9% (6/86).